Virus activation and immune function during intense training in rugby football players - Yamauchi, R.; Shimizu, K.; Kimura, F.; Takemura, M.; Suzuki, K.; Akama, T.; Kono, I.; Akimoto, T. (International Journal of Sports Medicine, 2011)
Epidemiological studies suggest that highly trained athletes are more susceptible to upper respiratory tract infections (URTI) compared with the general population. Upper respiratory symptoms (URS) often appear as either primary invasion of pathogenic organisms and/or reactivation of latent viruses such as Epstein-Barr virus (EBV). The purpose of this study was to examine the relationship between EBV reactivation and the appearance of URS during intensive training in collegiate rugby football players. We evaluated EBV-DNA expression in saliva and examined the relationship between onset of URS and daily changes in EBV-DNA as well as secretory immunoglobulin A (SIgA) levels among 32 male collegiate rugby football players during a 1-month training camp. The EBV-DNA expression tended to be higher in subjects who exhibited sore throat (p=0.07) and cough (p=0.18) than that of those who had no symptoms, although their differences were not significant. The SIgA level was significantly lower 1 day before the EBV-DNA expression (p<0.05). The number of URS increased along with the EBV-DNA expression and decrease of SIgA levels. These results suggest that the appearance of URS is associated with reactivation of EBV and reduction of SIgA during training.